Ancient Adaptive Lateral Gene Transfers in the Symbiotic Opalina–Blastocystis Stramenopile Lineage. (6th November 2019) - Yubuki, Naoji; Galindo, Luis Javier; Reboul, Guillaume; López-García, Purificación; Brown, Matthew W; Pollet, Nicolas; Moreira, David
Abstract: Lateral gene transfer is a very common process in bacterial and archaeal evolution, playing an important role in the adaptation to new environments. In eukaryotes, its role and frequency remain highly debated, although recent research supports that gene transfer from bacteria to diverse eukaryotes may be much more common than previously appreciated. However, most of this research focused on animals and the true phylogenetic and functional impact of bacterial genes in less-studied microbial eukaryotic groups remains largely unknown. Here, we have analyzed transcriptome data from the deep-branching stramenopile Opalinidae, common members of frog gut microbiomes, and distantly related to the well-known genus Blastocystis . Phylogenetic analyses suggest the early acquisition of several bacterial genes in a common ancestor of both lineages. Those lateral gene transfers most likely facilitated the adaptation of the free-living ancestor of the Opalinidae– Blastocystis symbiotic group to new niches in the oxygen-depleted animal gut environment.